2008
DOI: 10.1007/s12064-008-0022-3
|View full text |Cite
|
Sign up to set email alerts
|

Tree thinking cannot taken for granted: challenges for teaching phylogenetics

Abstract: Tree thinking is an integral part of modern evolutionary biology, and a necessary precondition for phylogenetics and comparative analyses. Tree thinking has during the 20th century largely replaced group thinking, developmental thinking and anthropocentricism in biology. Unfortunately, however, this does not imply that tree thinking can be taken for granted. The findings reported here indicate that tree thinking is very much an acquired ability which needs extensive training. I tested a sample of undergraduate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 32 publications
2
54
0
5
Order By: Relevance
“…Unfortunately, phylogenetic trees are not well understood by students (Baum et al 2005;Gregory 2008;Halverson 2010a;Meir et al 2007;Omland et al 2008;Sandvik 2008;Thanukos 2009). For example, students often misinterpret phylogenetic trees because they focus on superficial features.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Unfortunately, phylogenetic trees are not well understood by students (Baum et al 2005;Gregory 2008;Halverson 2010a;Meir et al 2007;Omland et al 2008;Sandvik 2008;Thanukos 2009). For example, students often misinterpret phylogenetic trees because they focus on superficial features.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tree thinking (the ability to understand evolution as a process of branching and rebranching) among the public in general, however, is not as accepted and widespread as one might expect. "Tree thinking is very much an acquired ability which needs extensive training" (Sandvik 2008), and even graduate students and professors of biology find it difficult to correctly interpret a simple tree drawing (Baum et al 2005;Bishop and Anderson 1986;Diamond and Scotchmoor 2006;Meir et al 2007a). There are at least three reasons for this absence of tree thinking: a general misunderstanding of the theory of evolution; a lack of familiarity with phylogenies; and a visual evolutionary culture which sustains an eminently progressive discourse full of prejudices that leads to wrong interpretations of the process (i.e., the widespread presence of traditional "trees of life").…”
Section: Problems Of Interpretationmentioning
confidence: 99%
“…For this reason, Baum et al (2005) recommend that evolution education include clear and explicit instruction on building trees as well as on reading relationships and traits depicted in phylogenetic trees. Although a wide range of research has identified students' difficulties with interpreting these trees (O'Hara 1997, Lopez et al 1997, Meir et al 2007, Novick and Catley 2007, Perry et al 2008, Sandvik 2008, only a few have explored students' abilities to construct them (Staub et al 2006, Halverson 2011. Our research has focused on students' abilities to construct phylogenetic trees from a set of familiar organisms.…”
Section: Introductionmentioning
confidence: 99%